2019
DOI: 10.1101/627877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotavirus Calcium Dysregulation Manifests as Dynamic Calcium Signaling in the Cytoplasm and Endoplasmic Reticulum

Abstract: 28 Like many viruses, rotavirus (RV) dysregulates calcium homeostasis by elevating 29 cytosolic calcium ([Ca 2+ ]cyt) and decreasing endoplasmic reticulum (ER) stores. While 30 an overall, monophasic increase in [Ca 2+ ]cyt during RV infection has been shown, the 31 nature of the RV-induced aberrant calcium signals and how they manifest over time at 32 the single-cell level have not been characterized. Thus, we generated cell lines and 33 human intestinal enteroids (HIEs) stably expressing cytosolic and/or ER-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…African green monkey kidney epithelial (MA104) cells were cultured in high glucose DMEM supplemented with 10% fetal bovine serum (FBS) at 37°C in 5% CO2. MA104 cells were engineered to stably express the GCaMP6s cytosolic calcium indicator (MA104-GCaMP6s) as previously described and maintained under 50 µg/mL hygromycin drug selection 20,21 . D6/2-rotavirus was propagated in MA104 cells in serum-free DMEM supplemented with 1 µg/mL Worthington's Trypsin (Worthington Biochemical).…”
Section: Cell Lines Mouse Intestinal Organoid Cultures and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…African green monkey kidney epithelial (MA104) cells were cultured in high glucose DMEM supplemented with 10% fetal bovine serum (FBS) at 37°C in 5% CO2. MA104 cells were engineered to stably express the GCaMP6s cytosolic calcium indicator (MA104-GCaMP6s) as previously described and maintained under 50 µg/mL hygromycin drug selection 20,21 . D6/2-rotavirus was propagated in MA104 cells in serum-free DMEM supplemented with 1 µg/mL Worthington's Trypsin (Worthington Biochemical).…”
Section: Cell Lines Mouse Intestinal Organoid Cultures and Virusesmentioning
confidence: 99%
“…Within virus-infected cells, intracellular NSP4 functions as a viral ion channel to release Ca 2+ from the endoplasmic reticulum, which initiates the reprogramming of cells for virus replication. Further, the NSP4-induced increase in Ca 2+ signaling in infected cells also induces the release of paracrine signals, which affect neighboring uninfected cells [15][16][17][18][19][20] . We recently showed that rotavirus infected cells exhibit robust Ca 2+ signaling, which drives increased extracellular purines that activate the purinergic receptor P2Y1 on neighboring cells, and results in a propagating "intercellular Ca 2+ wave" encompassing neighboring cells 21 .…”
Section: Introductionmentioning
confidence: 99%